Astronomy : - Fix, John D. (McGraw-Hill Higher Education, 2008)
Astronomy: Journey to the Cosmic Frontier, 5th edition, provides enough content and background in astronomy so the student will be able to follow current developments in astronomy years after they complete the course. The historical development of astronomy is emphasized to show that astronomy, like other sciences, advances through the efforts of many scientists, and to show how present ideas have been developed.